A Systematic Review and Meta-Analysis of Three Gene Variants Association with Risk of Prostate Cancer: An Update - Chen, Yu; Zhong, Huan; Gao, Jian-Guo; Tang, Jian-Er; Wang, Rongjiang (Urology Journal, 2015)
Purpose: Prostate cancer (PCa) is one of the most commonly diagnosed male malignancies. Numerous studies have investigated the role of genetic variants in PCa risk. However, the results remain unclear. The purpose of this study was to evaluate the relationship between single-nucleotide polymorphism (SNP) rs2228001 in xeroderma pigmentosum group C (XPC), SNP rs4073 in interleukin 8 (IL8), and SNP rs2279744 in mouse double minute 2 (MDM2) homolog gene with PCa susceptibility. Materials and Methods: Electronic database of PubMed, Medline, and Embase were searched for eligible articles published between January 2000 and April 2014. The odd ratio (OR) with its 95% confidence interval (CI) were calculated to estimate the strength of association. Results: A total 18 case-control studies, including 5725 PCa cases and 5900 healthy controls, were screened out. Six studies were eligible for each SNP. For XPC 939A/C polymorphism, no significant association was found with PCa risk in the whole population (P > .05). No relationship in subgroup analysis was found by ethnicity. For IL8 -251T/A variant, the A allele was not related with PCa risk in any genetic models when compared with those individuals without A allele. For MDM2 -309T/G mutation, the G allele was not associated with the increased risk of PCa in total population and subgroup analysis by ethnicity as well. Conclusion: Our study demonstrated that all these three genetic polymorphisms were not associated with an increased risk of developing PCa, which might also provide an insight into the future research. Further large-scale studies with concerning the gene-gene and gene-environment interactions are needed to elucidate final conclusion.